The Behavior of Sufi Adherents on Social Media and Their Interactions With Non-Sufi Muslims - Ridwan Olamilekan Mustapha (International Journal of Islamic Khazanah, 2024)
Tasawwuf (Sufism) is a mystical Islamic tradition that emphasizes soul purification, sincere devotion to Allah, and fostering harmonious relationships across ideological divides. This study investigates the nature and challenges of online interactions between Sufi and non-Sufi Muslims in Nigeria. Utilizing a descriptive research design, data were collected through a Google Form questionnaire and analyzed using frequency counts and percentages. A multistage sampling approach ensured the inclusion of respondents from diverse Sufi and non-Sufi groups. The findings reveal that while interactions between Sufi and non-Sufi Muslims are frequent, particularly on platforms like Facebook, they are often marked by contentious exchanges. Provocative statements directed at Sufi Muslims occasionally lead to tensions, although most Sufi respondents prefer to avoid confrontation by ignoring such provocations. However, concerns were raised regarding the online behavior of some Sufi youth, which appears to deviate from traditional Sufi teachings as they engage in arguments to defend Sufism. This study underscores the importance of enhanced spiritual guidance for Sufi adherents to align their online activities with the principles of Tasawwuf. Promoting respectful digital discourse and fostering mutual understanding are essential strategies to mitigate tensions and strengthen harmony within the broader Muslim community.